Women’s interest in Self-employment: Understanding the impact of Entrepreneurial Education, Skills, and Behaviors: Mediating Role of Entrepreneurial Intentions - Parveen , Sajida; Sheikh, Salman Masood; ur Rahman, Saif (Pakistan Journal of Humanities and Social Sciences, 2023)
Entrepreneurs all across the global community are exploring entrepreneurship as a means to build wealth, operate the economy, and satisfy their dream of independence.This research aims to shed light on entrepreneurial skills, entrepreneurial education, perceived behavior control, and perceived family support for the career success of entrepreneurs in Pakistan. A self-administered questionnaire was used to obtain data; all 166 responses were analyzed employing a technique known as partial least squares structural equation modeling (PLS-SEM).The findings of the study show that entrepreneurial skills and education have a more significant favorable impact on women's success in their careers where in the presence of intention, perceived behavior control is a unique predictor of career success make known to by this study. Furthermore, perceived family support is a substantial moderator of entrepreneurial intentions and career success is also another contribution of present study. According to the findings, entrepreneurial intentions are the most significant mediator between entrepreneurial attributes and the career success of women entrepreneurs. The government should implement programs to foster self-employment, provide financial support, and change the rules and regulations to allow individuals of all ages to establish their own businesses as a career. As a result, the labor ministry and social welfare agencies can get fresh insights through this research in order to boost the proportion of women to male labor in the global labor market.